A numerical simulation of wing walls using computational fluid dynamics - Mak, C.M.; Niu, J.L.; Lee, C.T.; Chan, K.F. (Energy and buildings, 2007)
Larger window openings in the walls of a building may provide better natural ventilation. However, it also increases the penetration of direct solar radiation into indoor environment. The use of wing wall, one of the green features, is an alternative to create effective natural ventilation. Givoni conducted experiments in a wind tunnel to study the ventilation performance of wing walls. This paper presents a numerical study of the ventilation performance of wing walls using computational fluid dynamics (CFD). Two-dimensional and three-dimensional simulations are compared with the results of the experiments of Givoni. The results indicate that wing wall can promote natural ventilation by increasing the air change per hour and the mean indoor air speed relative to wind speed at various wind speeds and wind directions. The best performance of wing wall is at the wind angle of around 45°. The study also shows that 3D CFD simulation produces similar trend to the experimental results though there are some discrepancies.